Catheter-directed therapy for pulmonary embolism in pediatrics: a systematic review and meta-analysis - Basel F. Alqeeq; Dina Essam Abo-elnour; Mohamed Rifai; Luis L. Gamboa; Ibrahim Qattea; Mohammed Hamzah; Khaled M. Al-Farawi; Alaa Ahmed Elshanbary; Ibrahim Kamal; Mohammed Alsabri (Thrombosis Journal)
Abstract Background Acute pulmonary embolism (PE) is a serious and potentially fatal condition that is relatively rare in the pediatric population. In patients presenting with massive/submassive PE, catheter-directed Therapy (CDT) presents an emerging therapeutic modality by which PE can be managed. Methods Electronic databases were systematically searched through May 2024. This systematic review was performed in line with recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement guidelines and was registered in PROSPERO (Reg. no. CRD42024534229). Results Sixteen case reports/series were included in the quantitative analysis with a total population of 40 children diagnosed with PE. Of them, 21 were females and 19 were males. Massive PE was diagnosed in 15 patients and submassive PE was diagnosed in 17 patients. Complete resolution of PE happened at a rate of 68% (95%CI = 46–80%). Mortality was encountered at a rate of 18% (95%CI = 0.7–36%). PE recurred after CDT at a rate of 15% (95%CI = 2–28%). Non-major bleeding complicated CDT at a rate of 46% (95%CI = 25–66%, p = 0.163). Conclusion CDT can be utilized in the management of PE in children as a potential therapeutic option for selected patients. While the results of CDT interventions for pediatric PE are promising, further research -including well-conducted cohort studies- is required to validate those results.